Dissolution Profiles of Lanoxin Tablets in Media Supplemented with Soluble and Insoluble Forms of Fiber - Michael A. Sandoval; Hugh D. Smyth; Jason T. McConville (Journal of Pharmacy and Nutrition Sciences, 2011)
Lanoxin (digoxin) is available as 125 µg or 250 µg tablets for oral administration used to treat heart failure and arrhythmias. The objective of this study was to develop and investigate a comparativedissolutionstudy performed on lanoxin tablets in presence of insoluble or soluble forms of fiber. This study was performed to understand possible influence of fiber (psyillium husk, wheat dextrin, or powdered cellulose)on dissolutionof lanoxin in physiological relevant temperature and pH.Dissolutiontesting was performed using a USP dissolution testing apparatus II paddlerotating at 100 r/min, in 600 mL simulated gastric fluid (pH 1.2) which was maintained at (37 +/- 0.5 °C). A floating cellulose dialysis tube was used to collect sampling fractions. Quantification was performed using a developed and validated high performance liquid chromatographic (HPLC) method. Results indicate that the presence of psyillium husk in the dissolution medium hindered digoxin release. Statistical results reveal that the release profiles of digoxin in presence of wheat dextrin or powdered cellulose did not influence drug release.